RETRACTION NOTICE: Model Kolaborasi Antar-lembaga dan Reformasi Tata Kelola Keamanan Maritim Dalam Menjaga Kedaulatan Indonesia Pasca Reformasi - Sudarto, Sudarto (Universitas Semarang, 2024)
RETRACTION TO: Sudarto Sudarto (2024). Model Kolaborasi Antar-lembaga dan Reformasi Tata Kelola Keamanan Maritim Dalam Menjaga Kedaulatan Indonesia Pasca Reformasi. Jurnal USM Law Review Vol 7, No 3, pp. 1260-1271, December 2024, DOI: 10.26623/julr.v7i3.8912. Following a rigorous, carefully concerned, and considered review of the article published in Jurnal USM Law Review to article entitled “Model Kolaborasi Antar-lembaga dan Reformasi Tata Kelola Keamanan Maritim Dalam Menjaga Kedaulatan Indonesia Pasca Reformasi” Jurnal USM Law Review Vol 7, No 3, pp. 1260-1271, December 2024, DOI: 10.26623/julr.v7i3.8912. Sudarto Sudarto. The article contains redundant material and copyright infringement. Following a report from the original author and an investigation conducted by the editor, it was found that the article bears similarities to a previously published article in the NUSANTARA: Jurnal Ilmu Pengetahuan Sosial Vol. 8 No. 5 (2021) DOI: 10.31604/jips.v8i6.2021.1406-1428, Ministrate Jurnal Birokrasi & Pemerintahan Vol 3. No. 1 (2021) DOI: https://doi.org/10.15575/jbpd.v3i3, Jurnal Kebijakan Sosial Ekonomi Kelautan dan Perikanan Vol. 13 No. 2 Jurnal Kebijakan Sosial Ekonomi Kelautan dan Perikanan Vol. 13 No 2 (2023) http://ejournal-balitbang.kkp.go.id/index.php/jkse/article/view/12542